Attenuation of fibroblast activation and fibrosis by adropin in systemic sclerosis - Liang, Minrui; Dickel, Nicholas; Györfi, Andrea Hermina; SafakTümerdem, Bilgesu; Li, Yi Nan; Rius Rigau, Aleix Rius; Liang, Chunguang; Hong, Xuezhi; Shen, Lichong; Matei, Alexandru-Emil; Trinh-Minh, Thuong; Tran-Manh, Cuong; et al. (Science Translational Medicine, 2024)
Fibrotic diseases impose a major socioeconomic challenge on modern societies and have limited treatment options. Adropin, a peptide hormone encoded by the energy homeostasis–associated (ENHO) gene, is implicated in metabolism and vascular homeostasis, but its role in the pathogenesis of fibrosis remains enigmatic. Here, we used machine learning approaches in combination with functional in vitro and in vivo experiments to characterize adropin as a potential regulator involved in fibroblast activation and tissue fibrosis in systemic sclerosis (SSc). We demonstrated consistent down-regulation of adropin/ENHO in skin across multiple cohorts of patients with SSc. The prototypical profibrotic cytokine TGFβ reduced adropin/ENHO expression in a JNK-dependent manner. Restoration of adropin signaling by therapeutic application of bioactive adropin34–76 peptides in turn inhibited TGFβ-induced fibroblast activation and fibrotic tissue remodeling in primary human dermal fibroblasts, three-dimensional full-thickness skin equivalents, mouse models of bleomycin-induced pulmonary fibrosis and sclerodermatous chronic graft-versus-host-disease (sclGvHD), and precision-cut human skin slices. Knockdown of GPR19, an adropin receptor, abrogated the antifibrotic effects of adropin in fibroblasts. RNA-seq demonstrated that the antifibrotic effects of adropin34–76 were functionally linked to deactivation of GLI1-dependent profibrotic transcriptional networks, which was experimentally confirmed in vitro, in vivo, and ex vivo using cultured human dermal fibroblasts, a sclGvHD mouse model, and precision-cut human skin slices. ChIP-seq confirmed adropin34–76-induced changes in TGFβ/GLI1 signaling. Our study characterizes the TGFβ-induced down-regulation of adropin/ENHO expression as a potential pathomechanism of SSc as a prototypical systemic fibrotic disease that unleashes uncontrolled activation of profibrotic GLI1 signaling.
CRIS-Team Scopus Importer:2024-04-05

CD19-CAR T-cell therapy induces deep tissue depletion of B cells - Tur, Carlo; Eckstein, Markus; Velden, Joachim; Rauber, Simon; Bergmann, Christina; Auth, Janina; Bucci, Laura; Corte, Giulia; Hagen, Melanie; Wirsching, Andreas; Grieshaber Bouyer, Ricardo; Reis, Petra; et al. (Annals of the Rheumatic Diseases, 2024)
Objectives CD19-targeting chimeric antigen receptor (CAR) T-cell therapy can induce long-term drug-free remission in patients with autoimmune diseases (AIDs). The efficacy of CD19-CAR T-cell therapy is presumably based on deep tissue depletion of B cells; however, such effect has not been proven in humans in vivo. Methods Sequential ultrasound-guided inguinal lymph node biopsies were performed at baseline and after CD19-CAR T-cell therapy in patients with AIDs. Results were compared with lymph node biopsies from rituximab (RTX)-treated AID patients with absence of peripheral B cells. Conventional and immunohistochemistry staining were performed on lymph node tissue to assess architecture as well the number of B cells, follicular dendritic cells (FDCs), plasma cells, T cells and macrophages. Results Sequential lymph node biopsies were analysed from five patients with AID before and after CD19-CAR T-cell therapy and from five patients with AID after RTX treatment. In addition, non-lymphoid organ biopsies (colon, kidney and gallbladder) from three additional patients with AID after CD19-CAR T-cell therapy were analysed. CD19+ and CD20+ B cells were completely depleted in the lymph nodes after CD19-CAR T-cell therapy, but not after RTX treatment. Plasma cells, T cells and macrophages in the lymph nodes remained unchanged. Follicular structures were disrupted and FDCs were depleted in the lymph nodes after CD19-CAR T-cell therapy, but not after RTX. Non-lymphoid organs were completely depleted of B cells. Discussion This study demonstrates complete B-cell depletion in secondary lymphoid tissues of patients with AIDs following CD19-CAR T-cell therapy combined with standard lymphodepleting therapy.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Autoimmune Diseases; B-Lymphocytes; Rituximab; Ultrasonography

Characterization of Vascular Niche in Systemic Sclerosis by Spatial Proteomics - Rius Rigau, Aleix Rius; Li, Yi Nan; Matei, Alexandru-Emil; Györfi, Andrea Hermina; Bruch, Peter Martin; Koziel, Sarah; Devakumar, Veda; Gabrielli, Armando; Kreuter, Alexander; Wang, Jiucun; Dietrich, Sascha; Schett, Georg; et al. (Circulation Research, 2024)
BACKGROUND: Systemic sclerosis (SSc) is a connective tissue disease that can serve as a model to study vascular changes in response to inflammation, autoimmunity, and fibrotic remodeling. Although microvascular changes are the earliest histopathologic manifestation of SSc, the vascular pathophysiology remains poorly understood. METHODS: We applied spatial proteomic approaches to deconvolute the heterogeneity of vascular cells at the single-cell level in situ and characterize cellular alterations of the vascular niches of patients with SSc. Skin biopsies of patients with SSc and control individuals were analyzed by imaging mass cytometry, yielding a total of 90755 cells including 2987 endothelial cells and 4096 immune cells. RESULTS: We identified 7 different subpopulations of blood vascular endothelial cells (VECs), 2 subpopulations of lymphatic endothelial cells, and 3 subpopulations of pericytes. A novel population of CD34+;αSMA+ (α-smooth muscle actin);CD31+ VECs was more common in SSc, whereas endothelial precursor cells were decreased. Co-detection by indexing and tyramide signal amplification confirmed these findings. The microenvironment of CD34+;αSMA+;CD31+ VECs was enriched for immune cells and myofibroblasts, and CD34+;αSMA+;CD31+ VECs expressed markers of endothelial-to-mesenchymal transition. The density of CD34+;αSMA+;CD31+ VECs was associated with clinical progression of fibrosis in SSc. CONCLUSIONS: Using spatial proteomics, we unraveled the heterogeneity of vascular cells in control individuals and patients with SSc. We identified CD34+;αSMA+;CD31+ VECs as a novel endothelial cell population that is increased in patients with SSc, expresses markers for endothelial-to-mesenchymal transition, and is located in close proximity to immune cells and myofibroblasts. CD34+;αSMA+;CD31+ VEC counts were associated with clinical outcomes of progressive fibrotic remodeling, thus providing a novel cellular correlate for the crosstalk of vasculopathy and fibrosis.
CRIS-Team Scopus Importer:2024-04-12
Keywords: endothelial cells; fibrosis; proteomics; scleroderma; systemic; vascular system injuries

Combination therapies of porcupine inhibition with ruxolitinib, ibrutinib, or belumosudil in murine sclerodermatous GVHD - Hong, Xuezhi; Xiao, Yanhua; Xu, Liyan; Shen, Lichong; Neelagar, Ranjana; Devakumar, Veda; Trinh-Minh, Thuong; Liang, Minrui; Rigau, Aleix Rius; Zhang, Yun; Li, Yi Nan; Dees, Clara; et al. (Blood Advances, 2025)
CRIS-Team Scopus Importer:2025-04-01

Combined inhibition of IL-1, IL-33 and IL-36 signalling by targeting IL1RAP ameliorates skin and lung fibrosis in preclinical models of systemic sclerosis - Grönberg, Caitríona; Rattik, Sara; Tran-Manh, Cuong; Zhou, Xiang; Rius Rigau, Aleix Rius; Li, Yi Nan; Györfi, Andrea Hermina; Dickel, Nicholas; Kunz, Meik; Kreuter, Alexander; Matei, Emil Alexandru; Zhu, Honglin; et al. (Annals of the Rheumatic Diseases, 2024)
Background: The interleukin (IL)-1 receptor accessory protein (IL1RAP) is an essential coreceptor required for signalling through the IL-1, IL-33 and IL-36 receptors. Here, we investigate the antifibrotic potential of the combined inhibition of these cytokines by an anti-IL1RAP antibody to provide a scientific background for clinical development in systemic sclerosis (SSc). Methods: The expression of IL1RAP-associated signalling molecules was determined by data mining of publicly available RNA sequencing (RNAseq) data as well as by imaging mass cytometry. The efficacy of therapeutic dosing of anti-IL1RAP antibodies was determined in three complementary mouse models: sclerodermatous chronic graft-versus-host disease (cGvHD), bleomycin-induced dermal fibrosis model and topoisomerase-I (topo)-induced fibrosis. Results: SSc skin showed upregulation of IL1RAP and IL1RAP-related signalling molecules on mRNA and protein level compared with normal skin. IL-1, IL-33 and IL-36 all regulate distinct gene sets related to different pathophysiological processes in SSc. The responses of human fibroblasts and endothelial cells to IL-1, IL-33 and IL-36 were completely blocked by treatment with an anti-IL1RAP antibody in vitro. Moreover, anti-IL1RAP antibody treatment reduced dermal and pulmonary fibrosis in cGvHD-induced, bleomycin-induced and topoisomerase-induced fibrosis. Importantly, RNAseq analyses revealed effects of IL1RAP inhibition on multiple processes related to inflammation and fibrosis that are also deregulated in human SSc skin. Conclusion: This study provides the first evidence for the therapeutic benefits of targeting IL1RAP in SSc. Our findings have high translational potential as the anti-IL1RAP antibody CAN10 has recently entered a phase one clinical trial.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Fibroblasts; Inflammation; Pulmonary Fibrosis; Scleroderma; Systemic

ENGRAILED 1 COORDINATES CYTOSKELETAL ORGANIZATION TO PROMOTE MYOFIBROBLAST DIFFERENTIATION AND FIBROTIC TISSUE REMODELING - Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Fuchs, Maximilian; Rigau, Aleix; Hong, Xuezhi; Honglin, Z.; Luber, M.; Bergmann, Christina; Dees, Clara; Ludolph, Ingo; Horch, Raymund E.; Distler, O.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2021)
CRIS-Team WoS Importer:2021-10-01

Engrailed 1 coordinates cytoskeletal reorganization to induce myofibroblast differentiation - Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Fuchs, Maximilian; Liang, Chunguang; Rigau, Aleix; Hong, Xuezhi; Zhu, Honglin; Luber, Markus; Bergmann, Christina; Dees, Clara; Ludolph, Ingo; Horch, Raymund E.; et al. (Journal of Experimental Medicine, 2021)
Transforming growth factor-β (TGFβ) is a key mediator of fibroblast activation in fibrotic diseases, including systemic sclerosis. Here we show that Engrailed 1 (EN1) is reexpressed in multiple fibroblast subpopulations in the skin of SSc patients. We characterize EN1 as a molecular amplifier of TGFβ signaling in myofibroblast differentiation: TGFβ induces EN1 expression in a SMAD3-dependent manner, and in turn, EN1 mediates the profibrotic effects of TGFβ. RNA sequencing demonstrates that EN1 induces a profibrotic gene expression profile functionally related to cytoskeleton organization and ROCK activation. EN1 regulates gene expression by modulating the activity of SP1 and other SP transcription factors, as confirmed by ChIP-seq experiments for EN1 and SP1. Functional experiments confirm the coordinating role of EN1 on ROCK activity and the reorganization of cytoskeleton during myofibroblast differentiation, in both standard fibroblast culture systems and in vitro skin models. Consistently, mice with fibroblast-specific knockout of En1 demonstrate impaired fibroblast-to-myofibroblast transition and are partially protected from experimental skin fibrosis.
CRIS-Team Scopus Importer:2021-07-30

Imaging mass cytometry-based characterisation of fibroblast subsets and their cellular niches in systemic sclerosis - Rigau, Aleix Rius; Liang, Minrui; Devakumar, Veda; Neelagar, Ranjana; Matei, Alexandru Emil; Györfi, Andrea Hermina; Bergmann, Christina; Filla, Tim; Fedorchenko, Vladyslav; Schett, Georg; Distler, Jörg; Li, Yi Nan (Annals of the Rheumatic Diseases, 2024)
Objectives Transcriptomic data demonstrated that fibroblasts are heterogeneous with functionally diverse subpopulations. Although fibroblasts are key effector cells of fibrotic diseases such as systemic sclerosis (SSc), they have not yet been characterised spatially at the cellular level. Here, we aimed to investigate fibroblast subpopulations using imaging mass cytometry (IMC) as a proteomic-based, spatially resolved omics approach. Methods We applied IMC to deconvolute the heterogeneity of 49 969 cells including 6501 fibroblasts at the single-cell level, to analyse their spatial distribution and to characterise their cellular niches in skin sections of patients with SSc and controls in situ. Results We identified 13 different subpopulations of fibroblasts in SSc and control skin, the proportion increases in five fibroblast subpopulations (myofibroblasts, FAPhigh, S1PR+, Thy1+;ADAM12high;PU.1high and ADAM12+;GLI1+ fibroblasts) and decreases in three subpopulations (TFAMhigh, PI16+;FAP+ and Thy1+;ADAM12low fibroblasts). Several fibroblast subpopulations demonstrated spatial enrichment and altered cellular interactions in SSc. The proportion of S1PR+-fibroblast positively correlated with more extensive skin fibrosis, whereas high numbers of PI16+;FAP–-fibroblasts were associated with milder skin fibrosis. The frequency of aberrant cellular interaction between S1PR+ and ADAM12+;GLI1+-fibroblasts also positively associated with the extent of skin fibrosis in SSc. Conclusion Using IMC, we demonstrated profound changes in composition and localisation of the majority of fibroblast subpopulations in SSc skin. These findings may provide a rationale for specific targeting of deregulated fibroblast subpopulations in SSc. Quantification of S1PR+-fibroblast and PI16+;FAP–fibroblasts may offer potential for patient stratification according to severity of skin fibrosis.
CRIS-Team Scopus Importer:2025-02-04

Mouse models of skin fibrosis - Rigau, Aleix; Luber, Markus; Distler, Jörg (Methods in Molecular Biology, 2021)
Systemic sclerosis (SSc) is a rare systemic autoimmune disease associated with a high mortality. The first histopathological hallmarks are vasculopathy and inflammation, followed by fibrosis of the skin and internal organs. The molecular and cellular mechanisms are incompletely understood. Rodent models provide important insights into the pathogenesis of SSc and are a mainstay for the development of novel targeted therapies. Here we describe the mechanistic insights of inducible and genetic models, and also discuss in detail the limitations and pitfalls of the most frequently used SSc mouse models. We also describe protocols for running the established bleomycin-induced scleroderma skin fibrosis model.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Bleomycin; Chronic graft-versus-host disease; Mouse model; Skin fibrosis; Systemic sclerosis

Mutual Amplification of GLI2/Hedgehog and Transcription Factor JUN/AP-1 Signaling in Fibroblasts in Systemic Sclerosis: Potential Implications for Combined Therapies - Bergmann, Christina; Chenguiti Fakhouri, Sara; Trinh-Minh, Thuong; Filla, Tim; Rius Rigau, Aleix Rius; Ekici, Arif Bülent; Merlevede, Benita; Hallenberger, Ludwig; Zhu, Honglin; Dees, Clara; Matei, Alexandru Emil; Auth, Janina; et al. (Arthritis and Rheumatology, 2024)
Objective: Deregulation of the cJUN/AP-1 and hedgehog/GLI2 signaling pathways has been implicated in fibroblast activation in systemic sclerosis (SSc). However, the consequences of their concomitant up-regulation are unknown. Here, we tested the hypothesis that mutual amplification of both pathways might drive persistent fibroblast activation. Methods: Cultured fibroblasts and skin sections of patients with diffuse SSc and healthy volunteers were analyzed. cJUN/AP-1 signaling and hedgehog/GLI2 signaling were inhibited using knockdown and pharmacologic approaches. Hedgehog signaling was activated in mice by fibroblast-specific overexpression of constitutively active Smoothened. Results: cJUN and GLI2 are concomitantly up-regulated and colocalize in fibroblasts of patients with SSc compared to healthy controls. Activation of hedgehog/GLI2 signaling induces the expression of cJUN in vitro and in vivo, whereas inactivation of GLI2 inhibits cJUN expression. Likewise, inactivation of cJUN impairs the expression of GLI2. This mutual regulation occurs at the level of transcription with binding of cJUN and GLI2 to specific binding motifs. Interference with this mutual amplification of cJUN signaling and GLI2 signaling inhibits fibroblast activation and collagen release: Inhibition of cJUN/AP-1 signaling ameliorates hedgehog-induced fibroblast activation and skin fibrosis in SmoACT mice with a reduction of skin thickness of 103% (P = 0.0043) in the treatment group compared to the fibrotic control group. Moreover, combined pharmacologic inhibition of cJUN/AP-1 and hedgehog/GLI2 exerts additive antifibrotic effects in a model of TGFβ-driven experimental fibrosis (TBRACT mice). Conclusion: The transcription factors cJUN and GLI2 reinforce each other's activity to promote fibroblast activation in SSc. Interruption of this crosstalk by combined inhibition of both pathways exerts additive antifibrotic effects at well-tolerated doses.
CRIS-Team Scopus Importer:2024-12-06

Neutrophils seeking new neighbors: radiotherapy affects the cellular framework and the spatial organization in a murine breast cancer model - Reichardt, Clara; Munoz Becerra, Marco; Rius Rigau, Aleix Rius; Rückert, Michael; Fietkau, Rainer; Schett, Georg; Gaipl, Udo; Frey, Benjamin; Munoz Becerra, Luis (Cancer Immunology, Immunotherapy, 2024)
Neutrophils are known to contribute in many aspects of tumor progression and metastasis. The presence of neutrophils or neutrophil-derived mediators in the tumor microenvironment has been associated with poor prognosis in several types of solid tumors. However, the effects of classical cancer treatments such as radiation therapy on neutrophils are poorly understood. Furthermore, the cellular composition and distribution of immune cells in the tumor is of increasing interest in cancer research and new imaging technologies allow to perform more complex spatial analyses within tumor tissues. Therefore, we aim to offer novel insight into intra-tumoral formation of cellular neighborhoods and communities in murine breast cancer. To address this question, we performed image mass cytometry on tumors of the TS/A breast cancer tumor model, performed spatial neighborhood analyses of the tumor microenvironment and quantified neutrophil-extracellular trap degradation products in serum of the mice. We show that irradiation with 2 × 8 Gy significantly alters the cellular composition and spatial organization in the tumor, especially regarding neutrophils and other cells of the myeloid lineage. Locally applied radiotherapy further affects neutrophils in a systemic manner by decreasing the serum neutrophil extracellular trap concentrations which correlates positively with survival. In addition, the intercellular cohesion is maintained due to radiotherapy as shown by E-Cadherin expression. Radiotherapy, therefore, might affect the epithelial–mesenchymal plasticity in tumors and thus prevent metastasis. Our findings underscore the growing importance of the spatial organization of the tumor microenvironment, particularly with respect to radiotherapy, and provide insight into potential mechanisms by which radiotherapy affects epithelial–mesenchymal plasticity and tumor metastasis.
CRIS-Team Scopus Importer:2024-03-15
Keywords: Cancer; Cellular neighborhood; Image mass cytometry; Neutrophil; Radiotherapy

TEMPORAL MIGRATION OF IMMUNE CELLS FROM PSORIATIC SKIN TO JOINTS INITIATING SYNOVIAL INFLAMMATION IN PSORIATIC ARTHRITIS - Raimondo, Maria Gabriella; Rauber, Simon; Xu, Cong; Mohammadian, Hashem; Vogg, Mario; Anchang, Charles Gwellem; Rigau, Aleix; Luber, M.; Labinsky, Hannah; Soare, A.; Distler, Jörg; Fearon, U.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04